Parametric Study Using a Braking Distance Simulation of an Anti-locked Braking System Vehicle - Kim, Sehun; Kim, Jongchan; Kim, Kiho; Kwon, Seongjin; Lee, Bonghuyn; Kang, Yonggu (Asian Journal of Chemistry, 2013)
Over the last century, the braking performance has become the core of vehicle research along with engine performance. The braking distance, which is a very important factor for evaluating the braking performance, is affected by the brake system of vehicles, tires and road friction characteristics. All the vehicles released recently should be equipped with an anti-locked braking system for stability. The anti-locked braking system is quite effective in shortening the braking distance. Therefore, studies in the past focused on the efficiency and method of the control logic for anti-locked braking system. As a result, the brake system was developed but there has been little research on the relationship between a vehicle with anti-locked braking system and the tire characteristics. In this paper, the tire characteristics were studied in terms of the brake distance of a vehicle equipped with an anti-locked braking system. To achieve this, the braking distance simulation method was first developed using a multi-body vehicle dynamic model including brake control logic and tire model and its confidence was verified by an outdoor braking test. The relationship between the tire characteristics and braking distance was analyzed by orthogonal arrays based on the design of experiments. Through tire indoor tests, the relationship between the tire characteristics and its structure design variables, such as tread and side-wall stiffness, were also analyzed. The effect of the tire on the braking performance of a vehicle equipped with anti-locked braking system was assessed.